PUISI BALI WINDU KARYA I GUSTI NGURAH RAI ANTARA [ANALISIS SEMIOTIKA] - I Gede Mardi Yasa (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
Literature is one of Balinese culture that is still relevant to be heard and implemented in today's life. Because in literature it contains an advice and the essence of life that should be done in the current era. Literature can be divided into two, namely traditional and modern literature. Both of these literatures are growing rapidly in the 4.0 era as it is today. Genaman today is a technology that is appropriate to be used to search for and study literary works that are the basis for carrying out social life. In the literature that has been divided into two that we know carefully and have felt in life. However, with the development of a literature, it is appropriate to give a meaning that is in accordance with the developing literature. Literature that is easy to find and learn is modern literature. Modern literature that can be divided into three is the novel, poetry, and poetry. Of the three, which can be given a touch of meaning in poetry. Poetry is a literary work that has a meaning that is stored behind a diction that is the star of the performance in the literary work.